The Impact of Health Administration on Healthcare Quality: A Systematic Review of Effective Management Practices - Majeed, Rawan Ahmed; Yamani, Heba Fahad; AlSharif, Maisa Hamza; Sindi, Sarah Saud; Aljohani , Rawan Yousef; Kalkatawi, Haneen Mohmed; Alqiri, Abeer Taher; Hawsawi , Halah Saleh; Alabdali, Manal Hammad; Noori , Abrar Abdulaziz (Journal of Ecohumanism, 2024)
Health administration plays a crucial role in shaping the quality of healthcare delivery by implementing effective management practices that enhance patient outcomes and operational efficiency. This systematic review aims to examine the impact of key administrative practices on healthcare quality, focusing on strategies that improve patient satisfaction, reduce errors, and optimize resource utilization. A comprehensive literature search was conducted across databases including PubMed, Scopus, and Google Scholar, reviewing studies published from 2016 onwards. Inclusion criteria targeted research on management practices such as resource allocation, leadership models, operational efficiency, and quality assurance systems. Findings indicate that health administration practices, particularly in leadership and operational efficiency, have a significant positive effect on quality metrics, such as reduced patient wait times, lower readmission rates, and increased patient satisfaction. However, challenges like limited resources and resistance to change often hinder implementation. This review underscores the need for adopting evidence-based administrative strategies and suggests directions for future research to further enhance healthcare quality through effective management practices.